Impact of Xpert MTB/RIF on Outcomes of Adults Hospitalized With Spinal Tuberculosis: Findings From a Comparative Cohort in Beijing, China - Fan, Jun; An, Jun; Shu, Wei; Tang, Kai; Shang, Yuanyuan; Xue, Yi; Qin, Shibing; Pang, Yu (Frontiers in Public Health, 2022)
Background: Spinal tuberculosis (TB) is one of the most common forms of extrapulmonary tuberculosis, causing increased morbidity and lifelong disabilities. Here, we conducted a retrospective study to determine the impact on patient outcomes of the Xpert MTB/RIF test versus phenotypical drug susceptibility testing for spinal TB. Methods: Spinal TB inpatients were enrolled in 2013 and 2017 at Beijing Chest Hospital. Data were collected from electronic patient record system that documented demographic and clinical characteristics. All the patients were routinely followed-up at 1, 3, 6, 9, 12 months after surgery during outpatient treatment. Results: A total of 361 patients affected by spinal TB were enrolled in our analysis, including 178 patients in 2013 and 183 patients in 2017. In 2013, the cumulative postoperative recurrence rate of spinal TB patients was 23.0% (41/178), which was significantly higher than that in 2017 (8.2%, 15/183, P<0.001). Additionally, the spinal TB patients diagnosed in 2013 relapsed significantly sooner than those in 2017 (P<0.001). In the multivariate analysis, rifampicin (RIF) resistance was associated with recurrence of spinal TB. The turnaround time of Xpert ranged from 1 to 3 days, with a median of 1 day (IQR: 1-2). For the phenotypic drug susceptibility test (pDST)-based algorithm, the median turnaround time was 67 days, considerably longer than that of the Xpert-based algorithm (P<0.001). Conclusion: RIF resistance is an independent risk factor for postoperative recurrence in spinal TB patients. Early detection of RIF resistance due to the application of Xpert is an effective strategy to reduce spinal TB recurrence.